Environmental Accounting and Economic Valuation of Natural Resources: The Impact of Commodity Extraction on Human Development in Producing Regions - Hastarini Dwi Atmanti (CV. Get Press Indonesia, 2026)
The paradoxical nexus between natural resource abundance and socio-economic progression remains a critical hurdle for extractive-dependent economies. This investigation scrutinizes the impact of commodity extraction on human development within producing regions through environmental accounting and economic valuation. Utilizing an explanatory longitudinal-cross-sectional design, the research evaluates secondary data from 64 regencies in Indonesia, synthesizing fiscal realization reports from the Ministry of Finance (Oil, Gas, and Mineral Revenue Sharing/DBH) with Human Development Index (HDI) metrics from Statistics Indonesia (BPS). The study employs panel data regression with fixed effects and double-log transformation to measure revenue-to-welfare elasticity. Results reveal a significant yet inelastic correlation (), indicating substantial revenue inflows fail to proportionately catalyze human welfare advancements. By calculating Net Present Value (NPV) of ecosystem service losses, findings identify an